Dramaturgy in Interpersonal Communication of Online Dating Application Users (Tinder) in Jakarta - Fitria, Namira (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This research is motivated by the rise of online dating applications used by the millennial generation in Jakarta. The Tinder application is an online dating application that is quite popular with the millennial generation. In this study, the researcher used a qualitative approach by choosing the Dramaturgy theory popularized by Goffman (1959). The study examines the creation of impressions (impression management) created by Tinder application users on the front stage and backstage. This study aims to determine how impression and message management is managed by Tinder application users in interpersonal communication. From this study, there are several different impressions from what is on the front stage and back stage